PENGARUH MODEL PEMBELAJARAN PROBLEM BASED INTRUCTION (PBI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA POKOK BAHASAN PERSAMAAN LINEAR SATU VARIABEL DI PONPES SALAPIAH GUNUNG SILAYANG LAYANG - awaludin hasibuan; Mohd arifin; susi sulastri lubis (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2021)
This study aims to determine the magnitude of the increase in students' mathematics learning outcomes through the Problem Based Instruction (PBI) learning model for learning mathematics with Single Variable Linear Equation System material in class VII Ponpes Salapiah Gunung Silayang-Layang for the academic year 2020-2021. This type of research is Classroom Action Research (CAR) which consists of 2 cycles. The subjects in this study were Class VII students at Ponpes Salapiah Gunung Silayang Layang Padangsidimpuan, on the material of linear equations of one variable. While the object of this research was the application of the Problem Based Instruction (PBI) Learning Model to the learning outcomes of mathematics at Ponpes Salapiah Gunung Silayang Layang Padangsidimpuan, on one variable linear equation material. The results showed that the ability of student learning outcomes in learning mathematics through the Problem Based Instruction (PBI) learning model of class VII-2 Islamic boarding school Salapiah Gunung Silayang-Layang in the One Variable Linear Equation material for the 2020/2021 school year increased by 71.85 with the category